Microsoft Azure DevOps Engineer Expert (AZ-400) Cert Prep: 1 Configure Processes and Communications by Microsoft Press. - Furlan, Paul; Press, Microsoft (linkedin.com, 2023)
Practice your skills and get ready for the first domain of the Azure DevOps Engineer Expert (AZ-400) certification exam.